2006
DOI: 10.1038/sj.ki.5001603
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular hyperfiltration predicts the development of microalbuminuria in stage 1 hypertension: The HARVEST

Abstract: Factors related to the development of microalbuminuria in hypertension are not well known. We did a prospective study to investigate whether glomerular hyperfiltration precedes the development of microalbuminuria in hypertension. We assessed 502 never-treated subjects screened for stage 1 hypertension without microalbuminuria at baseline and followed up for 7.8 years. Creatinine clearance was measured at entry. Urinary albumin and ambulatory blood pressure were measured at entry and during the follow-up until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 35 publications
4
74
0
3
Order By: Relevance
“…To account for the age-related decline in GFR, hyperfiltration was defined as GFR >130 ml min −1 1.73 m −2 minus 1 ml min −1 1.73 m −2 per year after the age of 40 [28]. Studies in hypertensive non-diabetic participants, using creatinine clearance as an index of GFR, have suggested that elevated GFR may be an indicator of early target organ damage [37,38]. In the PREVEND (Prevention of Renal and Vascular Disease) study, a community based study in 7,728 non-diabetic participants, GFR estimated by creatinine clearance was proportional to BMI [39] and elevated AER was independently associated with hyperfiltration assessed by creatinine clearance [40].…”
Section: Hyperfiltration Independent Of Diabetesmentioning
confidence: 99%
“…To account for the age-related decline in GFR, hyperfiltration was defined as GFR >130 ml min −1 1.73 m −2 minus 1 ml min −1 1.73 m −2 per year after the age of 40 [28]. Studies in hypertensive non-diabetic participants, using creatinine clearance as an index of GFR, have suggested that elevated GFR may be an indicator of early target organ damage [37,38]. In the PREVEND (Prevention of Renal and Vascular Disease) study, a community based study in 7,728 non-diabetic participants, GFR estimated by creatinine clearance was proportional to BMI [39] and elevated AER was independently associated with hyperfiltration assessed by creatinine clearance [40].…”
Section: Hyperfiltration Independent Of Diabetesmentioning
confidence: 99%
“…These cutoffs have been used previously to categorize CKD (5,20), and to define hyperfiltration (21).…”
Section: Evaluation Of the Estimated Gfrmentioning
confidence: 99%
“…In the general population, the systolic blood pressure and fasting glucose appear to be the most important factors related to MAB, through their direct effect on the glomerular intra-renal pressure or the stimulation of the renin-angiotensin-aldosterone system [19]. Inflammation, endothelial dysfunction and thrombogenic factors have been implicated as potential mechanisms underlying the relationship between proteinuria and cardiovascular disease [20].…”
Section: @Erspublicationsmentioning
confidence: 99%